Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45450
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Method for Turbulent Flows in Highly Staggered and Low Solidity Supersonic Turbine Cascades

Abstract: Two main problems are associated with conventional numerical methods for simulating turbulent flows in high-reaction-type supersonic turbine cascades near the tip of the last stage blade in a steam turbine: the large skewness of computational grids and treatments of boundary conditions when the shock waves hit boundaries. This paper presents a numerical method to deal with these issues. A grid generation technique which uses five-block structured grids has been developed. The orthogonality of the grid is good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It offers advantages, for example, better understanding of flow features related to turbine profiles, and quick and less expensive process. Recently, a number of numerical investigations deal with turbine blade boundary layer flow characteristics, wake passing effects, blade profile loss prediction, flow control on turbine blade profiles, design optimization methods for blade profiles, and so on, using RANS 91,92 (Figures 16 and 17), LES, 30 or even DNS 93 (Figure 18).…”
Section: Research Methods Of Axial Turbine Blade Profile Aerodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It offers advantages, for example, better understanding of flow features related to turbine profiles, and quick and less expensive process. Recently, a number of numerical investigations deal with turbine blade boundary layer flow characteristics, wake passing effects, blade profile loss prediction, flow control on turbine blade profiles, design optimization methods for blade profiles, and so on, using RANS 91,92 (Figures 16 and 17), LES, 30 or even DNS 93 (Figure 18).…”
Section: Research Methods Of Axial Turbine Blade Profile Aerodynamicsmentioning
confidence: 99%
“…Therefore, although the RANS results are quite promising, there is still space for performance improvement in the transition and turbulence models, especially in low Reynolds number applications. 91,92 As the computational power increases, the application of LES becomes more popular for understanding the complex flow physics of turbine blade profiles, and to overcome the deficiencies of RANS simulations. Since the LES method is inherently an unsteady analysis and capable of time-dependent capturing of highly resolved motions associated with blade separated flows, it does not contain any transition modeling, regardless of separation-induced or disturbance-induced ones.…”
Section: Research Methods Of Axial Turbine Blade Profile Aerodynamicsmentioning
confidence: 99%
“…Features of three types of aerofoils are described as follows. Mach number contours for subsonic aerofoils near the hub are calculated by a two-dimensional (2D) turbulent flow analysis code, which is the internally developed CFD software named TURBO2D (Senoo and White, 2006;Senoo et al, 2011), and shown in Fig. 11.…”
Section: Blade Designmentioning
confidence: 99%